The Relationship between Cancer and Paraoxonase 1 - Irma Martha Medina-Díaz; Néstor Ponce-Ruíz; Aurora Elizabeth Rojas-García; José Francisco Zambrano-Zargoza; Yael Y. Bernal-Hernández; Cyndia Azucena González-Arias; Briscia S. Barrón-Vivanco; José Francisco Herrera-Moreno (MDPI AG, 2022)
Extensive research has been carried out to understand and elucidate the mechanisms of paraoxonase 1 (PON1) in the development of diseases including cancer, cardiovascular diseases, neurological diseases, and inflammatory diseases. This review focuses on the relationship between PON1 and cancer. The data suggest that PON1, oxidative stress, chronic inflammation, and cancer are closely linked. Certainly, the gene expression of PON1 will remain challenging to study. Therefore, targeting PON1, redox-sensitive pathways, and transcription factors promise prevention and therapy in the development of several diseases, including cancer.